The Effect of Transactional Leadership Application on Employee Performance Through Work Motivation - Robert Sanjaya Sembiring; Prihatin Lumbanraja; Yeni Absah (AIBPM Publisher, 2024)
This study aim to explain and analyze the influence of transactional leadership on employee performance through motivation as an intervening variable in PT Wira Duta FiberGlass Deli Serdang. The population of this research data is all employees PT Wira Duta FiberGlass Deli Serdang totaling 46 people and sampling using a census. Data collection methods using questionnaires with SEM Smart PLS software as a data analysis tool. The results showed that there was a positive and significant relationship between transactional leadership on employee performance, transactional leadership on work motivation, work motivation on employee performance, and transactional leadership on employee performance mediated by work motivation. Hopefully PT Wira Duta FiberGlass Deli Serdang can continue to evaluate in improving the leadership system to employees through good and equal contijen rewards, then create an active and passive supervision system that makes employees comfortable in order to provide satisfactory performance for the company